The banality of evil (REVISTA NODO, 2025)
The banality of evil is presented as the thought hidden in the shadows; it is the "artificial intelligence" that throws us into plagiarism, apathy, and the obvious. We must resort to technopoetics, which are presented as strategies of imbalance, of doubt, of pondering in the face of the wave of technological thought, in the face of the unreflective invasion of technologies into the everyday. It is pausing to reflect in the face of synthesized intelligences. I return to texts that confront us with corporality and thought to find the fractures in the face of the drowning of information, to find the critical eye, the flaws in imposed visions.